Effects of Milk Feeding Strategy and Acidification on Growth Performance, Metabolic Traits, Oxidative Stress, and Health of Holstein Calves - Alugongo, Gibson Maswayi; Xiao, Jianxin; Azarfar, Arash; Liu, Shuai; Yousif, Mohammed Husien; Ma, Yulin; Wang, Yangjing; Li, Shengli; Cao, Zhijun (Frontiers in Animal Science, 2022)
Holstein calves (N = 48; 12 calves/treatment) were assigned to 1 of 4 treatments in a 2 × 2 factorial arrangement of milk feeding strategy [6 L/d (MOD) or 12 L/d (HIGH) of milk] and acidification [non-acidified milk (NAM) or acidified milk (ACM)] at d 2. Calves were bucket fed milk as follows: 6 L/d from d 3 to 49 for MOD and 6 L/d from d 3 to 6, 12 L/d from d 7 to 42 and 8 L/d from d 43 to 49 for HIGH calves. All calves were then fed 4 L/d from d 50 to 56. Calves had access to starter and water ad libitum, while hay was fed at 5 % of starter from d 64. Calves were weighed, measured and blood (except d 14, 42 and 56) sampled on d 2, 14, 28, 42, 49, 56, 63 and 78. We detected a milk feeding strategy × time interaction for starter intake, body weight, ADG, ADG/ME, FE and all structural measurements. Although, overall (558.0 vs 638.6 g/d), the HIGH calves tended to consume fewer starter compared to MOD, significant differences were only observed in week 8. The HIGH calves had greater ADG during d 2 to 14 (1.12 vs 0.75 kg/d) and tended to have greater ADG at d 15 to 28 (0.79 vs 0.55) and 29 to 42 (0.86 vs 0.60) and lower at d 57 to 63 (0.11 vs. 0. 38) compared to MOD calves. The HIGH calves had greater BW from d 28 to 78 compared to MOD, while NAM were bigger compared to ACM calves from d 49 to 78. The HIGH calves had lower overall feed and metabolizable energy efficiencies compared to MOD. Except for BW and heart girth, no milk acidification × time interaction were observed for starter intake, ADG, FE or ADG/ME. Blood glucose in calves fed NAM-HIGH and ACM-HIGH were greater compared to those fed moderate milk volumes at d 28 only. Although, the feeding strategy had no effect, acidified milk lowered the occurrence of diarrhea (odds ratio = 1.32) compared to those fed non-acidified milk.